The Association Between Mindfulness Facets and Substance Use via Emotional Psychopathology and Coping Motives in Argentinian College Students - Pilatti, Angelina (2024)
Fil: Pilatti, Angelina. Universidad Nacional de Córdoba. Facultad de Psicología; Argentina.